Panggilan Untuk Mengajar: Harapan Terhadap Pendidik Katolik Dalam Berbagai Dokumen Magisterium Gereja - Rikardus Jehaut (STIPAS St. Sirilus Ruteng, 2019)
The Church has consistently recognized that catholic teachers have an essential role in Catholic education and must serve as witnesses to the faith, in both word and deed. The constant appreciation for the role of catholic teachers is presented in the Church’s magisterial teachings. A review of these teachings provides understanding of the importance of the Catholic teacher and the teacher ’s role in fulfilling the mission of the Church by preparing students to live virtuous lives in service to society and the Church. The Second Vatican Council’s Declaration on Christian Education, Gravissimum Educationis, outlines the basic principles of Christian education, acknowledging the Church’s reliance on Catholic educators and the importance of preparation in secular and religious knowledge. Twelve years later, the impact of cultural and social pluralism on Catholic education was addressed by the Vatican’s Sacred Congregation for Education in The Catholic School. Supported by these and other magisterial documents, this article explicates the teachings of the Catholic Church summarizing the role of lay Catholic teachers and their qualifications; relationship to the Church; and Gospel witness, the spiritual and professional qualifications required of teachers to effectively impart an authentic Catholic education, expectations associated with apostolic witness and conduct of an authentic Christian role model. The purpose of the article is to provide an account of the expectations and qualities deemed important by the Church for teachers to maintain strong Catholic identity in schools and thereby fulfill the mission of the Church in this apostolate.